Figure drawing for concept artists - Muftic, Kan (3dtotalPublishing, 2017)
"Accessibly written and lavishly illustrated by respected concept artist Kan Muftic, this book celebrates the common ground between traditional life drawing and the fast-paced world of the concept art industry. Learn about the skills, techniques, and mindset needed to make successful life drawings, how to capture the forms of the human body on paper, and how to improve your character and concept art with a dynamic approach to figures and anatomy. Figure drawings for concept artists offers a unique up-to-date perspective on classical skills with the contemporary practitioner in mind." -- Provided by publisher.